Which smokers use the smoking cessation Quitline in Hong Kong, and how effective is the Quitline?. Issue 4 (24th November 2004) - Abdullah, A S M; Lam, T-H; Chan, S S C; Hedley, A J
Abstract : Objective: To describe the characteristics of the Chinese subjects who utilised the first telephone smoking cessation service in Hong Kong, and to evaluate its effectiveness. Methods: The Quitline provided Hong Kong residents with free telephone smoking cessation services which was publicised through a press conference, media reports, pamphlets, and posters at public and private hospitals and clinics. Callers who completed an initial interview from 13 December 2000 to 31 May 2002 were included. Smokers were interviewed using a structured record sheet and provided with stage matched counselling. A follow up interview was carried out after six months. Analysis was conducted by intention-to-treat. Results: Of the 1120 callers who completed initial assessments, 1047 were current smokers and 872 consented to follow ups. Compared to the general smoking population, the Quitline attracted more of those who were female, younger, single, unemployed, higher educated, smoking more than 20 cigarettes per day, and those with quitting experience. At six months, 12% (95% confidence interval 10% to 15%) of the participants reported that they had not smoked a cigarette for the past seven days. A stepwise logistic regression model showed that the use of nicotine replacement therapy at the present attempt to quit, having made one or more serious attempts to quit in the past, perceiving less difficulties in quitting, and smoking the first cigarette at age 15 years or above were significant predictors of quitting. Conclusion: This first Quitline in Asia appears to be acceptable to Chinese smokers, with quit rate comparable to those of better funded Quitlines in the West. A low cost Quitline is a promising model for smoking cessation services in the East.